PENINGKATAN KREATIVITAS DAN HASIL BELAJAR IPS DENGAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GIMKIT - Lufiyanti, Leny; Parji; Sudarmiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the application of problem-based learning models assisted by gimkit media in improving creativity and learning outcomes of class VII students of SMP Negeri 11 Kota Madiun. This study is a classroom action research. Data collection techniques use student creativity assessment rubrics and student learning outcome data. The data analysis method is descriptive qualitative. The results of the study showed that student creativity in the pre-cycle percentage of success was only 46.48% with a sufficient category, in cycle 1 the success indicator increased to 63.67% with a creative or good category, and in cycle 2 it increased to a success percentage reaching 82.81% with a very good or very creative category. Student learning outcomes in the pre-cycle percentage of completeness or success only reached 40.62%, in cycle I student completeness only reached 71.87% or around 23 students who completed above KKTP, while in cycle II there was a significant increase to 29 students who completed above KKTP or the percentage of completeness or success reached 90.62% and experienced an increase of 18.75%. Keywords: Problem Based Learning, Concrete Media Counting Glasses, Learning Outcomes.